Environment-friendly synthetic ammonia production process
Through an improved synthetic ammonia production process, utilizing aerospace furnace semi-waste boiler gasification and composite combustion aids, combined with isothermal transformation and PSA systems, using activated carbon-molecular sieve composite adsorbents and carbon nanotube-loaded ruthenium-based catalysts, the high energy consumption, high pollution and low efficiency problems of the traditional synthetic ammonia process have been solved, achieving low-carbon, environmentally friendly and efficient production.
Patent Information
- Application Number
- CN202511277137.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-10-14
- Estimated Expiration
- 2045-09-09
AI Technical Summary
The traditional ammonia synthesis process has the characteristics of high energy consumption, high pollution, large carbon emissions, difficulty in handling by-products, and easy poisoning of catalysts, resulting in high production costs and low efficiency.
The 6.5MPa aerospace furnace semi-waste pot gasification technology and CaO-Fe2O3-K2CO3 composite combustion aid are used, combined with a sulfur-resistant isothermal conversion system and a four-tower PSA system, using activated carbon-molecular sieve composite adsorbent, and carbon nanotube-loaded ruthenium-based catalyst in the ammonia synthesis link to optimize the hydrogen-nitrogen ratio and achieve efficient purification and catalysis.
It improves the utilization rate of raw coal, reduces by-products such as tar, increases CO conversion rate and single-pass conversion rate, reduces energy consumption and carbon emissions, extends catalyst life, and improves production efficiency.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of synthetic ammonia production, and in particular relates to an environmentally friendly synthetic ammonia production process. Background Art
[0002] Synthetic ammonia, a core product of the modern chemical industry, serves as a fundamental raw material for fertilizers, pharmaceuticals, dyes, explosives, and other applications. Its production scale and technological advancement are directly linked to agricultural safety and industrial development. However, traditional ammonia synthesis processes have long faced challenges such as high energy consumption, high pollution levels, and significant carbon emissions.
[0003] In the traditional coal-to-ammonia process, some small and medium-sized units still use fixed gasification technology, which has problems such as low gasification temperature and incomplete reaction, and is accompanied by by-products such as tar and phenols. These by-products not only increase the load on subsequent purification processes, but also easily cause equipment blockage and catalyst poisoning. At the same time, the treatment of organic matter such as tar requires additional energy consumption, further increasing production costs. In addition, the traditional gasification process lacks the regulation of efficient combustion aids, the activation energy of the coal-coke reaction is high, and the oxygen-coal ratio is not properly matched, resulting in low effective gas yield per unit of raw coal and serious energy waste. In the conversion process of crude synthesis gas, some older plants still use Fe-Cr catalysts and single-stage conversion, which have problems such as insufficient CO conversion rate and high steam consumption. Although modern plants use sulfur-resistant Co-Mo catalysts, they still need to optimize the steam / CO ratio to reduce energy consumption. During the purification process, traditional PSA systems have limited efficiency in removing trace organic sulfur (such as COS) and inert gases (such as CH4), requiring subsequent deep purification. Furthermore, the adsorbent's lifespan is shortened by sulfur permeation or micropore clogging. The adsorbent is also susceptible to sulfur poisoning or pore clogging, which can shorten its lifespan. The core of the ammonia synthesis reaction is the catalyst. Traditional iron-based catalysts must operate under high temperature and high pressure, resulting in high energy consumption and low single-pass conversion rates. This requires large amounts of recycle gas compression, further increasing energy consumption. Traditional PSA systems have limited efficiency in removing trace organic sulfur (such as COS) and inert gases (such as CH4), requiring subsequent deep purification. Furthermore, the adsorbent's lifespan is shortened by sulfur permeation or micropore clogging.
[0004] Based on this, it is urgent to develop a new ammonia synthesis process with low carbon, low pressure and high raw material tolerance. Summary of the Invention
[0005] The purpose of the present invention is to provide an environmentally friendly synthetic ammonia production process in response to existing problems.
[0006] The present invention is achieved through the following technical solutions:
[0007] An environmentally friendly synthetic ammonia production process comprises the following steps:
[0008] S1. The raw coal is dried and crushed into 80-120 mesh, and a composite combustion aid with a mass fraction of 1-3% is added and mixed evenly. Then, the raw coal is fed into a 6.5MPa pressure-grade aerospace furnace semi-waste boiler gasifier with an oxygen-coal ratio of 1:0.8-1 to undergo gasification treatment to generate crude synthesis gas.
[0009] S2: After the raw synthesis gas is dusted by the Venturi scrubber, it enters the sulfur-resistant isothermal conversion system, where it undergoes a two-stage isothermal conversion under the action of a Co-Mo catalyst to control the outlet CO content to ≤0.6%;
[0010] S3. The crude synthesis gas treated in step S2 is fed into a four-tower PSA system to remove CO2 and sulfide at an operating pressure of 2-3 MPa and an adsorption temperature of 40-60°C to obtain a mixed gas of H2 and N2. The mixed gas is then fed into a cryogenic separation system to be distilled and purified at -180°C and 0.5-1 MPa to obtain a refined gas.
[0011] S4. Green hydrogen is added to the above-mentioned refined gas, and the hydrogen-nitrogen ratio is adjusted to 2.8-3:1. After being pressurized to 15 MPa by a compressor, it is sent to an ammonia synthesis tower to synthesize ammonia under the action of a carbon nanotube-supported ruthenium-based catalyst.
[0012] Furthermore, the composite combustion-supporting agent in step S1 is CaO-Fe2O3-K2CO3, and the mass ratio of the three is 6:3:1;
[0013] The temperature of the gasification treatment is 1400-1600° C., and the gasification time is 4-6 seconds.
[0014] Furthermore, the specific parameters of the two-stage isothermal transformation described in step S2 are:
[0015] First-stage conversion: catalyst model is K8-11, operating temperature is 240~280℃, steam / CO ratio is 1.8~2.2, outlet CO concentration is ≤3%;
[0016] Second-stage conversion: The catalyst model is QDB-04, the operating temperature is 200~220℃, the steam / CO ratio is 1.2~1.5, and the outlet CO concentration is ≤0.6%.
[0017] Furthermore, the four-tower PSA system described in step S3 uses an activated carbon-molecular sieve composite adsorbent, and the adsorption cycle is 60-90 seconds.
[0018] Furthermore, the preparation of the activated carbon-molecular sieve composite adsorbent comprises the following steps:
[0019] S3-1. Add activated carbon: 13X molecular sieve: rice hull diatom in a mass ratio of 3:7:2 to deionized water at a solid-liquid ratio of 1:5-7, stir and mix, then add 2% of the total weight of the raw materials to cellulase, and carry out enzymatic hydrolysis at 45-55° C. and a stirring speed of 100-200 rpm for 4-5 hours. Then, vacuum freeze-dry at -50° C. and a vacuum degree of 10 Pa for 10-12 hours. After drying, pass through an 80-mesh sieve to obtain an adsorbent matrix;
[0020] S3-2, the adsorbent matrix and the chitosan-lignin mixed solution were mixed in a mass ratio of 9:1, stirred until a uniform plastic slurry was formed, and extruded through a circular die with a diameter of 3 mm using a screw extruder. The adsorbent blanks were cut into strips with a length of 5-8 mm using a cutting machine and naturally dried;
[0021] S3-3, placing the green body in a DBD plasma reactor, introducing helium gas, and performing plasma treatment;
[0022] S3-4. Prepare 0.5~0.6mol / L Ce(NO3)3 solution, immerse the plasma-treated body into the solution, ultrasonically immerse for 30~40min, take it out and drain it, then dry it at 70~80℃ for 4~5h, then place it in a tubular furnace, and in a N2 atmosphere, heat it to 400℃ at 2~3℃ / min, keep it warm for 2~3h, and then cool it naturally to room temperature.
[0023] Furthermore, the chitosan-lignin mixed solution in step S3-2 has a mass ratio of chitosan to lignin of 1:1 and a solid content of 20%.
[0024] Furthermore, the amount of helium introduced in step S3-3 is 50-60 mL / min, the power is controlled to be 500 W during the plasma treatment, and the treatment time is 20-25 min.
[0025] Furthermore, the green hydrogen described in step S4 is produced by electrolysis of water, and the hydrogen purity is ≥99.99%.
[0026] Furthermore, the preparation of the carbon nanotube-supported ruthenium-based catalyst described in step S4 comprises the following steps:
[0027] S4-1, placing multi-walled carbon nanotubes in a DBD plasma reactor, and introducing an Ar / O2 mixed gas for plasma treatment;
[0028] S4-2, ultrasonically dispersing the plasma-treated multi-walled carbon nanotubes in ethanol to prepare a 0.1 g / mL multi-walled carbon nanotube suspension;
[0029] RuCl3·3H2O was dissolved in ethanol to prepare a 0.1 mol / L ruthenium precursor solution, and 0.5 wt% HCOOH was added as a reduction promoter;
[0030] S4-3. Pump the multi-walled carbon nanotube suspension and the ruthenium precursor solution separately into the Y-shaped microchannel of the microfluidizer, controlling the flow rate ratio to 1:3 (CNT (carbon nanotube) liquid:ruthenium liquid). Directional mixing is performed under laminar flow. A 1 MHz ultrasonic standing wave field is activated with an amplitude of 10 μm. The standing wave pressure nodes are used to drive the ruthenium ions to precisely adsorb on the defect sites of the multi-walled carbon nanotubes. The residence time of the mixed solution in the microchannel is controlled to 120-130 s, ensuring a ruthenium ion adsorption rate of 99%.
[0031] S4-4, transferring the CNT-ruthenium precursor mixture after microfluidic loading to a supercritical CO2 reactor, sealing it, introducing supercritical CO2, raising the pressure in the reactor to 15 MPa, controlling the temperature at 40°C, and carrying out the reduction reaction in a supercritical CO2 atmosphere for 1.5-2.5 hours. Then, reducing the pressure to normal pressure at a rate of 0.5 MPa / min, collecting the solid product Ru / CNTs, and vacuum drying it at 55-65°C for 2-3 hours;
[0032] S4-5, the vacuum-dried Ru / CNTs were dispersed in ethanol, KNO3 and pyrrole monomer were added, and after stirring for 30-40 min, 0.1 mol / L FeCl3 solution was added dropwise to initiate polymerization. The reaction was allowed to proceed at room temperature for 2-3 h to form polypyrrole-K + film-coated CNTs;
[0033] The coated sample was transferred to a tube furnace and heated to 600°C at a rate of 5°C / min under an argon atmosphere (flow rate 40 mL / min) and kept at this temperature for 1.5-2.5 h. The polypyrrole was carbonized to form a nitrogen-doped carbon shell. + confined within the carbon shell.
[0034] Furthermore, during the plasma treatment in step S4-1, the volume ratio of Ar to O2 in the Ar / O2 mixed gas is 95:5;
[0035] The gas flow rate was controlled to be 40-50 mL / min, the power to be 300 W, and the processing time to be 20-30 min.
[0036] Furthermore, it also includes the treatment of three wastes and resource recovery: gasification waste residue is used as building material raw material after vitrification treatment; wastewater is treated by three-stage flash evaporation-double membrane method to achieve closed-loop circulation; CO2 desorbed by the PSA system is directly converted into product gas with a purity of ≥99.9%; and the active components of the deactivated catalyst are recovered through solvent extraction.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] The present invention adopts 6.5MPa aerospace furnace semi-waste pot gasification technology, combined with CaO-Fe2O3-K2CO3 composite combustion aid and optimizes the oxygen-coal ratio to achieve efficiency improvement from the source. The composite combustion aid uses CaO to fix sulfur, Fe2O3 to reduce the activation energy of coal char reaction, and K2CO3 to catalyze carbon-CO2 reaction, synergistically improving the coal conversion rate. The ultra-high temperature of 1400~1600℃ fully cracks tar, phenols and other macromolecules, avoids subsequent equipment blockage, and has a high utilization rate of raw coal. The present invention uses an isothermal transformation system to achieve precise CO conversion. The first stage uses K8-11 high activity to quickly convert most of the CO. The second stage uses QDB-04 low temperature activity to deeply convert the remaining CO. The four-tower PSA system uses activated carbon-molecular sieve composite adsorbents, combined with deep cold separation to achieve deep purification. In the ammonia synthesis link, carbon nanotubes are loaded with ruthenium-based catalysts as the core. The carbon nanotubes are treated with plasma to form defect sites. Ultrasonic standing waves drive the precise loading of ruthenium ions. Supercritical CO2 reduction controls the size of ruthenium particles. Nitrogen-doped carbon shells and K + Confinement enhances electron transfer, significantly improving the catalytic activity of the catalyst, and combined with green hydrogen to optimize the hydrogen-nitrogen ratio, effectively improving the single-pass conversion rate and increasing product yield. DETAILED DESCRIPTION
[0039] In order to further explain the present invention, it is described below with reference to the following specific embodiments.
[0040] Example 1
[0041] An environmentally friendly synthetic ammonia production process comprises the following steps:
[0042] S1. The raw coal is dried and crushed to 80 mesh, and a composite combustion aid of CaO-Fe2O3-K2CO3 (mass ratio of the three is 6:3:1) is added and mixed evenly. Then, the raw coal is mixed with oxygen with a purity of ≥99.6% at an oxygen-to-coal ratio of 1:0.8 and fed into a 6.5MPa pressure-rated aerospace furnace semi-waste boiler gasifier for gasification treatment at 1400°C for 4s to generate crude synthesis gas.
[0043] S2: After the raw synthesis gas is dusted by the Venturi scrubber, it enters the sulfur-resistant isothermal conversion system, where it undergoes a two-stage isothermal conversion under the action of a Co-Mo catalyst to control the outlet CO content to ≤0.6%;
[0044] The specific parameters of the two-stage isothermal transformation are:
[0045] First-stage conversion: catalyst model is K8-11, operating temperature is 240°C, steam / CO ratio is 1.8, outlet CO concentration is ≤3%;
[0046] Second-stage conversion: catalyst model is QDB-04, operating temperature is 200°C, steam / CO ratio is 1.2, outlet CO concentration is ≤0.6%;
[0047] S3. The crude synthesis gas treated in step S2 is fed into a four-tower PSA system to remove CO2 and sulfide at an operating pressure of 2-3 MPa and an adsorption temperature of 40°C to obtain a mixed gas of H2 and N2. The mixed gas is then fed into a cryogenic separation system to be distilled and purified at -180°C and 0.5 MPa to obtain a refined gas.
[0048] Activated carbon-molecular sieve composite adsorbent was used, and the adsorption cycle was 60s;
[0049] The preparation of the activated carbon-molecular sieve composite adsorbent comprises the following steps:
[0050] S3-1. Add activated carbon: 13X molecular sieve: rice hull diatom in a mass ratio of 3:7:2 to deionized water at a solid-liquid ratio of 1:5, stir and mix, then add 2% of the total weight of the raw materials to cellulase, incubate at 45°C and 100 rpm for 4 h, then freeze-dry at -50°C and 10 Pa vacuum for 10 h, and pass through an 80-mesh sieve after drying to obtain an adsorbent matrix;
[0051] S3-2. The adsorbent matrix and a chitosan-lignin mixed solution (the chitosan-lignin mixed solution has a chitosan-lignin mass ratio of 1:1 and a solid content of 20%) are mixed at a mass ratio of 9:1 and stirred until a uniform plastic slurry is formed. The slurry is extruded through a circular die with a diameter of 3 mm using a screw extruder, and then cut into 5 mm long strips of adsorbent blanks using a cutting machine, and then naturally dried.
[0052] S3-3, placing the green body in a DBD plasma reactor, introducing helium at a rate of 50 mL / min, controlling the power to 500 W, and treating for 20 min;
[0053] S3-4, prepare 0.5 mol / L Ce(NO3)3 solution, immerse the green body after plasma treatment in the solution, ultrasonically immerse for 30 minutes, take out and drain after completion, then dry at 70℃ for 4 hours, then place in a tube furnace, in N2 atmosphere, heat to 400℃ at 2℃ / min, keep warm for 2 hours, and then cool naturally to room temperature;
[0054] S4. Green hydrogen (hydrogen produced by electrolysis of water, with a hydrogen purity of ≥99.99%) is added to the above-mentioned refined gas, and the hydrogen-nitrogen ratio is adjusted to 2.8:1. The gas is pressurized to 15 MPa by a compressor and then fed into an ammonia synthesis tower to synthesize ammonia under the action of a carbon nanotube-supported ruthenium-based catalyst;
[0055] The preparation of the carbon nanotube-supported ruthenium-based catalyst comprises the following steps:
[0056] S4-1. Placing multi-walled carbon nanotubes in a DBD plasma reactor and introducing an Ar / O2 mixed gas for plasma treatment, wherein the volume ratio of Ar to O2 in the Ar / O2 mixed gas is 95:5, the gas flow rate is controlled at 40 mL / min, the power is 300 W, and the treatment time is 20 min;
[0057] S4-2, ultrasonically dispersing the plasma-treated multi-walled carbon nanotubes in ethanol to prepare a 0.1 g / mL multi-walled carbon nanotube suspension;
[0058] A 0.1 mol / L ruthenium precursor solution was prepared by dissolving RuCl3·3H2O in ethanol and adding 0.5 wt% HCOOH as a reduction promoter;
[0059] S4-3. Pump the multi-walled carbon nanotube suspension and the ruthenium precursor solution into the Y-shaped microchannel of the microfluidizer, controlling the flow rate ratio to 1:3 (CNT liquid:ruthenium liquid). Directed mixing is performed under laminar flow. A 1 MHz ultrasonic standing wave field is activated with an amplitude of 10 μm. The standing wave pressure nodes are used to drive the ruthenium ions to precisely adsorb on the defect sites of the multi-walled carbon nanotubes. The residence time of the mixed solution in the microchannel is controlled to 120-130 s, ensuring a ruthenium ion adsorption rate of 99%.
[0060] S4-4, transfer the CNT-ruthenium precursor mixture after microfluidic loading to a supercritical CO2 reactor, seal it, and introduce supercritical CO2 (density 0.8g / cm 3 ), raise the pressure in the autoclave to 15 MPa, control the temperature at 40°C, react for 1.5 h, then reduce the pressure to normal pressure at a rate of 0.5 MPa / min, collect the solid product, and vacuum dry it at 55°C for 2 h;
[0061] S4-5, the reduced Ru / CNTs were dispersed in ethanol, KNO3 and pyrrole monomer were added, stirred for 30 min, and 0.1 mol / L FeCl3 solution was added dropwise to initiate polymerization. The reaction was carried out at room temperature for 2 h to form polypyrrole-K + film-coated CNTs;
[0062] The coated sample was transferred to a tube furnace and heated to 600°C at a rate of 5°C / min under an argon atmosphere (flow rate 40 mL / min) and kept at this temperature for 1.5 h. The polypyrrole was carbonized to form a nitrogen-doped carbon shell. + confined within the carbon shell.
[0063] Example 2
[0064] An environmentally friendly synthetic ammonia production process comprises the following steps:
[0065] S1. The raw coal is dried and crushed to 80 mesh, and a composite combustion aid of CaO-Fe2O3-K2CO3 (mass ratio of the three is 6:3:1) is added and mixed evenly. Then, the raw coal is mixed with oxygen with a purity of ≥99.6% at an oxygen-to-coal ratio of 1:0.9 and fed into a 6.5 MPa pressure-rated aerospace furnace semi-waste boiler gasifier for gasification treatment at 1500°C for 5 seconds to generate crude synthesis gas.
[0066] S2: After the raw synthesis gas is dusted by the Venturi scrubber, it enters the sulfur-resistant isothermal conversion system, where it undergoes a two-stage isothermal conversion under the action of a Co-Mo catalyst to control the outlet CO content to ≤0.6%;
[0067] The specific parameters of the two-stage isothermal transformation are:
[0068] First-stage conversion: catalyst model is K8-11, operating temperature is 260°C, steam / CO ratio is 2, outlet CO concentration is ≤3%;
[0069] Second-stage conversion: catalyst model is QDB-04, operating temperature is 210°C, steam / CO ratio is 1.3, outlet CO concentration is ≤0.6%;
[0070] S3. The crude synthesis gas treated in step S2 is fed into a four-tower PSA system to remove CO2 and sulfide at an operating pressure of 2.5 MPa and an adsorption temperature of 50°C to obtain a mixed gas of H2 and N2. The mixed gas is then fed into a cryogenic separation system to be distilled and purified at -180°C and 0.7 MPa to obtain a refined gas.
[0071] Using activated carbon-molecular sieve composite adsorbent, the adsorption cycle is 60~90s;
[0072] The preparation of the activated carbon-molecular sieve composite adsorbent comprises the following steps:
[0073] S3-1. Add activated carbon: 13X molecular sieve: rice hull diatom in a mass ratio of 3:7:2 to deionized water at a solid-liquid ratio of 1:6, stir and mix, then add 2% of the total weight of the raw materials into cellulase, and incubate at 50°C and 150 rpm for 4.5 hours for enzymatic hydrolysis, followed by freeze-drying at -50°C and a vacuum degree of 10 Pa for 11 hours. After drying, sieve through an 80-mesh sieve to obtain an adsorbent matrix.
[0074] S3-2. The adsorbent matrix and a chitosan-lignin mixed solution (the chitosan-lignin mixed solution has a chitosan-lignin mass ratio of 1:1 and a solid content of 20%) are mixed at a mass ratio of 9:1 and stirred until a uniform plastic slurry is formed. The slurry is extruded through a circular die with a diameter of 3 mm using a screw extruder, and cut into 6 mm long strips of adsorbent blanks using a cutting machine, and then naturally dried.
[0075] S3-3. Place the green body in a DBD plasma reactor, introduce helium at a rate of 55 mL / min, control the power to 500 W, and process for 22 minutes;
[0076] S3-4, prepare 0.55 mol / L Ce(NO3)3 solution, immerse the green body after plasma treatment in the solution, ultrasonically immerse for 35 minutes, take out and drain after completion, then dry at 75℃ for 4.5 hours, then place in a tube furnace, in N2 atmosphere, heat to 400℃ at 2.5℃ / min, keep warm for 2.5 hours, and then cool naturally to room temperature;
[0077] S4. Green hydrogen (hydrogen produced by water electrolysis, with a hydrogen purity of ≥99.99%) is added to the above-mentioned refined gas, and the hydrogen-nitrogen ratio is adjusted to 2.9:1. The gas is pressurized to 15 MPa by a compressor and then fed into an ammonia synthesis tower to synthesize ammonia under the action of a carbon nanotube-supported ruthenium-based catalyst;
[0078] The preparation of the carbon nanotube-supported ruthenium-based catalyst comprises the following steps:
[0079] S4-1. Placing multi-walled carbon nanotubes in a DBD plasma reactor and introducing an Ar / O2 mixed gas for plasma treatment, wherein the volume ratio of Ar to O2 in the Ar / O2 mixed gas is 95:5, the gas flow rate is controlled at 45 mL / min, the power is 300 W, and the treatment time is 25 min;
[0080] S4-2, ultrasonically dispersing the plasma-treated multi-walled carbon nanotubes in ethanol to prepare a 0.1 g / mL multi-walled carbon nanotube suspension;
[0081] A 0.1 mol / L ruthenium precursor solution was prepared by dissolving RuCl3·3H2O in ethanol and adding 0.5 wt% HCOOH as a reduction promoter;
[0082] S4-3. Pump the multi-walled carbon nanotube suspension and the ruthenium precursor solution into the Y-shaped microchannel of the microfluidizer, controlling the flow rate ratio to 1:3 (CNT liquid:ruthenium liquid). Directed mixing was performed under laminar flow. A 1 MHz ultrasonic standing wave field was activated with an amplitude of 10 μm. The standing wave pressure nodes were used to drive the ruthenium ions to precisely adsorb on the defect sites of the multi-walled carbon nanotubes. The residence time of the mixed solution in the microchannel was controlled to 125 s, ensuring a ruthenium ion adsorption rate of 99%.
[0083] S4-4, transfer the CNT-ruthenium precursor mixture after microfluidic loading to a supercritical CO2 reactor, seal it, and introduce supercritical CO2 (density 0.8g / cm 3 ), raise the pressure in the autoclave to 15 MPa, control the temperature at 40°C, react for 2 h, then reduce the pressure to normal pressure at a rate of 0.5 MPa / min, collect the solid product, and vacuum dry it at 60°C for 2.5 h;
[0084] S4-5, the reduced Ru / CNTs were dispersed in ethanol, KNO3 and pyrrole monomer were added, stirred for 35 min, and 0.1 mol / L FeCl3 solution was added dropwise to initiate polymerization, and the reaction was carried out at room temperature for 2.5 h to form polypyrrole-K + film-coated CNTs;
[0085] The coated sample was transferred to a tube furnace and heated to 600°C at a rate of 5°C / min under an argon atmosphere (flow rate 40 mL / min) and kept at this temperature for 2 h. The polypyrrole was carbonized to form a nitrogen-doped carbon shell. + confined within the carbon shell.
[0086] Example 3
[0087] An environmentally friendly synthetic ammonia production process comprises the following steps:
[0088] S1. The raw coal is dried and crushed to 120 mesh, and a composite combustion aid of CaO-Fe2O3-K2CO3 (mass ratio of the three is 6:3:1) is added and mixed evenly. Then, the raw coal is mixed with oxygen with a purity of ≥99.6% at an oxygen-to-coal ratio of 1:1 and fed into a 6.5MPa pressure-rated aerospace furnace semi-waste boiler gasifier for gasification treatment at 1600°C for 6s to generate crude synthesis gas.
[0089] S2: After the raw synthesis gas is dusted by the Venturi scrubber, it enters the sulfur-resistant isothermal conversion system, where it undergoes a two-stage isothermal conversion under the action of a Co-Mo catalyst to control the outlet CO content to ≤0.6%;
[0090] The specific parameters of the two-stage isothermal transformation are:
[0091] First-stage conversion: catalyst model is K8-11, operating temperature is 280°C, steam / CO ratio is 2.2, outlet CO concentration is ≤3%;
[0092] Second-stage conversion: catalyst model is QDB-04, operating temperature is 220°C, steam / CO ratio is 1.5, outlet CO concentration is ≤0.6%;
[0093] S3. The crude synthesis gas treated in step S2 is fed into a four-tower PSA system to remove CO2 and sulfide at an operating pressure of 3 MPa and an adsorption temperature of 60°C to obtain a mixed gas of H2 and N2. The mixed gas is then fed into a cryogenic separation system to undergo rectification and purification at -180°C and 1 MPa to obtain a refined gas.
[0094] Activated carbon-molecular sieve composite adsorbent was used, and the adsorption cycle was 90s;
[0095] The preparation of the activated carbon-molecular sieve composite adsorbent comprises the following steps:
[0096] S3-1. Add activated carbon: 13X molecular sieve: rice hull diatom in a mass ratio of 3:7:2 to deionized water at a solid-liquid ratio of 1:7, stir and mix, then add 2% of the total weight of the raw materials to cellulase, incubate at 55°C and 200 rpm for 4-5 hours, then freeze-dry at -50°C and a vacuum degree of 10 Pa for 12 hours, and after drying, sieve through an 80-mesh sieve to obtain an adsorbent matrix;
[0097] S3-2. The adsorbent matrix and a chitosan-lignin mixed solution (the chitosan-lignin mixed solution has a chitosan-lignin mass ratio of 1:1 and a solid content of 20%) are mixed at a mass ratio of 9:1 and stirred until a uniform plastic slurry is formed. The slurry is extruded through a circular die with a diameter of 3 mm using a screw extruder, and cut into 8 mm long strips of adsorbent blanks using a cutting machine, and then naturally dried.
[0098] S3-3, placing the green body in a DBD plasma reactor, introducing helium at a rate of 60 mL / min, controlling the power to 500 W, and treating for 25 min;
[0099] S3-4, prepare 0.6 mol / L Ce(NO3)3 solution, immerse the green body after plasma treatment in the solution, ultrasonically immerse for 40 minutes, take out and drain after completion, then dry at 80℃ for 5 hours, then place in a tube furnace, and heat to 400℃ at 3℃ / min under N2 atmosphere, keep warm for 3 hours, and then cool naturally to room temperature;
[0100] S4. Green hydrogen (hydrogen produced by electrolysis of water, with a hydrogen purity of ≥99.99%) is added to the above-mentioned refined gas, and the hydrogen-nitrogen ratio is adjusted to 3:1. The gas is pressurized to 15 MPa by a compressor and then fed into an ammonia synthesis tower to synthesize ammonia under the action of a carbon nanotube-supported ruthenium-based catalyst;
[0101] The preparation of the carbon nanotube-supported ruthenium-based catalyst comprises the following steps:
[0102] S4-1. Placing multi-walled carbon nanotubes in a DBD plasma reactor and introducing an Ar / O2 mixed gas for plasma treatment, wherein the volume ratio of Ar to O2 in the Ar / O2 mixed gas is 95:5, the gas flow rate is controlled to be 50 mL / min, the power is 300 W, and the treatment time is 30 min;
[0103] S4-2, ultrasonically dispersing the plasma-treated multi-walled carbon nanotubes in ethanol to prepare a 0.1 g / mL multi-walled carbon nanotube suspension;
[0104] RuCl3·3H2O was dissolved in ethanol to prepare a 0.1 mol / L ruthenium precursor solution, and 0.5 wt% HCOOH was added as a reduction promoter;
[0105] S4-3. Pump the multi-walled carbon nanotube suspension and the ruthenium precursor solution into the Y-shaped microchannel of the microfluidizer, controlling the flow rate ratio to 1:3 (CNT liquid:ruthenium liquid). Directed mixing is performed under laminar flow. A 1 MHz ultrasonic standing wave field is activated with an amplitude of 10 μm. The standing wave pressure nodes are used to drive the ruthenium ions to precisely adsorb on the defect sites of the multi-walled carbon nanotubes. The residence time of the mixed solution in the microchannel is controlled to 130 s, ensuring a ruthenium ion adsorption rate of 99%.
[0106] S4-4, transfer the CNT-ruthenium precursor mixture after microfluidic loading to a supercritical CO2 reactor, seal it, and introduce supercritical CO2 (density 0.8g / cm 3 ), raise the pressure in the autoclave to 15 MPa, control the temperature at 40°C, react for 2.5 hours, then reduce the pressure to normal pressure at a rate of 0.5 MPa / min, collect the solid product, and vacuum dry it at 65°C for 3 hours;
[0107] S4-5, the Ru / CNTs after reduction were dispersed in ethanol, KNO3 and pyrrole monomer were added, stirred for 40 min, and 0.1 mol / L FeCl3 solution was added dropwise to initiate polymerization. The reaction was carried out at room temperature for 3 h to form polypyrrole-K + film-coated CNTs;
[0108] The coated sample was transferred to a tube furnace and heated to 600°C at a rate of 5°C / min under an argon atmosphere (flow rate 40 mL / min) and kept at this temperature for 2.5 h. The polypyrrole was carbonized to form a nitrogen-doped carbon shell.+ confined within the carbon shell.
[0109] Comparative Example 1
[0110] Compared with Example 2, in Comparative Example 1, no composite combustion aid is added in step S1, and the other steps are the same as those in Example 2.
[0111] Comparative Example 2
[0112] Compared with Example 2, this comparative example 2 replaces the two-stage isothermal transformation in step S2 with the first-stage transformation, omitting the second-stage transformation. The other steps are the same as those in Example 2.
[0113] Comparative Example 3
[0114] Compared with Example 2, this Comparative Example 3 is the same as Example 2, except that the activated carbon-molecular sieve composite adsorbent in step S3 is replaced with pure 13X molecular sieve.
[0115] Comparative Example 4
[0116] Compared with Example 2, in this Comparative Example 4, step S4-1 is omitted in the preparation of the carbon nanotube-supported ruthenium-based catalyst, and the other steps are the same as those in Example 2.
[0117] Test and Inspection
[0118] 1. Detection Method
[0119] Gas composition: A gas chromatograph (Agilent 7890A) was used to detect the contents of H2, CO, CO2, N2, and CH4;
[0120] Sulfide: H2S is measured by iodine titration, COS is measured by gas chromatography-sulfur chemiluminescence detector (GC-SCD);
[0121] Tar content: isopropyl alcohol absorption-gravimetric method;
[0122] Ammonia conversion: dilute sulfuric acid absorption-acid-base titration method;
[0123] Carbon emissions: CO2 emissions per unit of ammonia (kg / t) calculated using the carbon balance method.
[0124] 2. Test results
[0125] The experimental comparison data are shown in Table 1 below.
[0126] Table 1 Comparison of key performance and environmental indicators of various embodiments and comparative examples of environmentally friendly synthetic ammonia production process
[0127] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[粗合成气有效气(H2+CO)含量(%)]]> 88.5 89.2 90.1 78.5 89.0 89.1 89.2 Raw syngas tar content (mg / m 3 ) 15.2 12.5 10.8 45.8 12.6 12.7 12.5 CO content at conversion outlet (%) 0.58 0.52 0.49 0.55 2.8 0.53 0.52 <![CDATA[PSA出口CO2脱除率(%)]]> 99.1 99.3 99.5 99.2 99.3 92.5 99.3 PSA outlet sulfide removal rate (%) 99.8 99.9 99.9 99.8 99.9 95.2 99.9 Ammonia single-pass conversion rate (%) 24.8 25.6 26.2 24.2 23.8 25.5 19.3 Catalyst activity retention rate (after 100h, %) 95.8 96.5 97.2 95.8 95.2 90.2 62.5 <![CDATA[单位氨CO2排放量(kg / t)]]> 1280 1250 1230 1420 1320 1260 1255
[0128] It can be concluded from Table 1 above that in Comparative Example 1, no composite combustion-supporting agent was added, and the effective gas content in the crude synthesis gas decreased by 12%, and the tar content increased by 266%, indicating that the composite combustion-supporting agent can synergistically improve the gasification efficiency and reduce the generation of by-products; in Comparative Example 2, the secondary conversion was omitted, and the outlet CO increased from 0.52% to 2.8%, and the ammonia single-pass conversion rate decreased by 9.7%, indicating that the two-stage conversion setting can achieve deep conversion of CO and effectively avoid CO poisoning of the synthesis catalyst; in Comparative Example 3, pure 13X molecular sieve was used to replace the composite adsorbent, and the CO2 removal rate decreased from 99.3% to 92.5%, and the sulfide removal rate decreased from 99.9% to 95.2%, indicating that compared with the composite adsorbent, the pure 13X molecular sieve has insufficient selectivity for complex impurities; in Comparative Example 4, carbon nanotube plasma treatment was omitted, and the ammonia single-pass conversion rate decreased by 24.6%, and the activity retention rate decreased by 35.2%, indicating that the plasma treatment can enhance the anchoring effect of ruthenium ions and carbon nanotubes, and the activity is high.
[0129] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An environmentally friendly synthetic ammonia production process, characterized in that: The steps include: S1. The raw coal is dried and crushed into 80-120 mesh, and a composite combustion aid with a mass fraction of 1-3% is added and mixed evenly. Then, the raw coal is fed into a 6.5MPa pressure-grade aerospace furnace semi-waste boiler gasifier with an oxygen-coal ratio of 1:0.8-1 to undergo gasification treatment to generate crude synthesis gas. S2: After the raw synthesis gas is dusted by the Venturi scrubber, it enters the sulfur-resistant isothermal conversion system, where it undergoes a two-stage isothermal conversion under the action of a Co-Mo catalyst to control the outlet CO content to ≤0.6%; S3. The crude synthesis gas treated in step S2 is fed into a four-tower PSA system to remove CO2 and sulfide at an operating pressure of 2-3 MPa and an adsorption temperature of 40-60°C to obtain a mixed gas of H2 and N2. The mixed gas is then fed into a cryogenic separation system to be distilled and purified at -180°C and 0.5-1 MPa to obtain a refined gas. S4. Green hydrogen is added to the above-mentioned refined gas, and the hydrogen-nitrogen ratio is adjusted to 2.8-3:
1. After being pressurized to 15 MPa by a compressor, it is sent to an ammonia synthesis tower to synthesize ammonia under the action of a carbon nanotube-supported ruthenium-based catalyst.
2. The environmentally friendly synthetic ammonia production process according to claim 1, characterized in that: The composite combustion-supporting agent in step S1 is CaO-Fe2O3-K2CO3, and the mass ratio of the three is 6:3:1; The temperature of the gasification treatment is 1400-1600° C., and the gasification time is 4-6 seconds.
3. The environmentally friendly synthetic ammonia production process according to claim 1, characterized in that: The specific parameters of the two-stage isothermal transformation described in step S2 are: First-stage conversion: catalyst model is K8-11, operating temperature is 240~280℃, steam / CO ratio is 1.8~2.2, outlet CO concentration is ≤3%; Second-stage conversion: The catalyst model is QDB-04, the operating temperature is 200~220℃, the steam / CO ratio is 1.2~1.5, and the outlet CO concentration is ≤0.6%.
4. The environmentally friendly synthetic ammonia production process according to claim 1, characterized in that: The four-tower PSA system described in step S3 uses an activated carbon-molecular sieve composite adsorbent, and the adsorption cycle is 60-90 seconds.
5. The environmentally friendly synthetic ammonia production process according to claim 4, characterized in that: The preparation of the activated carbon-molecular sieve composite adsorbent comprises the following steps: S3-1. Add activated carbon: 13X molecular sieve: rice hull diatom in a mass ratio of 3:7:2 to deionized water at a solid-liquid ratio of 1:5-7, stir and mix, then add 2% of the total weight of the raw materials to cellulase, and carry out enzymatic hydrolysis at 45-55° C. and a stirring speed of 100-200 rpm for 4-5 hours. Then, vacuum freeze-dry at -50° C. and a vacuum degree of 10 Pa for 10-12 hours. After drying, pass through an 80-mesh sieve to obtain an adsorbent matrix; S3-2, the adsorbent matrix and the chitosan-lignin mixed solution were mixed in a mass ratio of 9:1, stirred until a uniform plastic slurry was formed, and extruded through a circular die with a diameter of 3 mm using a screw extruder. The adsorbent blanks were cut into strips with a length of 5-8 mm using a cutting machine and naturally dried; S3-3, placing the green body in a DBD plasma reactor, introducing helium gas, and performing plasma treatment; S3-4. Prepare 0.5~0.6mol / L Ce(NO3)3 solution, immerse the plasma-treated body into the solution, ultrasonically immerse for 30~40min, take it out and drain it, then dry it at 70~80℃ for 4~5h, then place it in a tubular furnace, and in a N2 atmosphere, heat it to 400℃ at 2~3℃ / min, keep it warm for 2~3h, and then cool it naturally to room temperature.
6. The environmentally friendly synthetic ammonia production process according to claim 5, characterized in that: The chitosan-lignin mixed solution in step S3-2 has a mass ratio of chitosan to lignin of 1:1 and a solid content of 20%.
7. The environmentally friendly synthetic ammonia production process according to claim 5, characterized in that: The amount of helium introduced in step S3-3 is 50-60 mL / min, the power is controlled to 500 W during plasma treatment, and the treatment time is 20-25 min.
8. The environmentally friendly synthetic ammonia production process according to claim 1, characterized in that: The green hydrogen described in step S4 is produced by electrolysis of water, and the hydrogen purity is ≥99.99%.
9. The environmentally friendly synthetic ammonia production process according to claim 1, characterized in that: The preparation of the carbon nanotube-supported ruthenium-based catalyst described in step S4 comprises the following steps: S4-1, placing multi-walled carbon nanotubes in a DBD plasma reactor, and introducing an Ar / O2 mixed gas for plasma treatment; S4-2, ultrasonically dispersing the plasma-treated multi-walled carbon nanotubes in ethanol to prepare a 0.1 g / mL multi-walled carbon nanotube suspension; RuCl3·3H2O was dissolved in ethanol to prepare a 0.1 mol / L ruthenium precursor solution, and 0.5 wt% HCOOH was added as a reduction promoter; S4-3, pumping the multi-walled carbon nanotube suspension and the ruthenium precursor solution into the Y-shaped microchannel of the microfluidic reactor separately, controlling the flow rate ratio of carbon nanotube liquid:ruthenium liquid to be 1:3, turning on a 1 MHz ultrasonic standing wave field with an amplitude of 10 μm, and controlling the residence time of the mixed solution in the microchannel to be 120-130 s; S4-4, transferring the carbon nanotube-ruthenium precursor mixture after microfluidic loading to a supercritical CO2 reactor, sealing it, introducing supercritical CO2, raising the pressure in the reactor to 15 MPa, controlling the temperature at 40°C, and carrying out a reduction reaction in a supercritical CO2 atmosphere for 1.5-2.5 hours, then reducing the pressure to normal pressure at a rate of 0.5 MPa / min, collecting the solid product Ru / carbon nanotubes, and vacuum drying it at 55-65°C for 2-3 hours; S4-5, the above vacuum-dried Ru / carbon nanotubes were dispersed in ethanol, KNO3 and pyrrole monomer were added, and after stirring for 30-40 minutes, 0.1 mol / L FeCl3 solution was added dropwise to initiate polymerization, and the reaction was carried out at room temperature for 2-3 hours to form polypyrrole-K + film-coated carbon nanotubes; The coated sample was transferred to a tube furnace and heated to 600°C at a rate of 5°C / min under an argon atmosphere and kept at this temperature for 1.5-2.5h to carbonize the polypyrrole to form a nitrogen-doped carbon shell. + confined within the carbon shell.
10. The environmentally friendly synthetic ammonia production process according to claim 9, characterized in that: During the plasma treatment in step S4-1, the volume ratio of Ar to O2 in the Ar / O2 mixed gas is 95:5; The gas flow rate was controlled to be 40-50 mL / min, the power to be 300 W, and the processing time to be 20-30 min.
Citation Information
Patent Citations
Fire coal synergist
CN102311835A
Isobaric ammonia synthesis and carbon-containing chemical co-production process
CN107043089A
High-efficient synthetic ammonia production process
CN108910914A
Device and method for synthetic ammonia isothermal shift
CN109534288A
Method for preparing carbon nanotube supported nanometer hydrated ruthenium oxide
CN1806914A